Predictors of sudden cardiac death in high‐risk patients following a myocardial infarction. (16th January 2020) - Docherty, Kieran F.; Ferreira, João Pedro; Sharma, Abhinav; Girerd, Nicolas; Gregson, John; Duarte, Kevin; Petrie, Mark C.; Jhund, Pardeep S.; Dickstein, Kenneth; Pfeffer, Marc A.; Pitt, Bertram; Rossignol, Patrick; et al.
Abstract: Aims: To develop a risk model for sudden cardiac death (SCD) in high‐risk acute myocardial infarction (AMI) survivors. Methods and results: Data from the Effect of Carvedilol on Outcome After Myocardial Infarction in Patients With Left Ventricular Dysfunction trial (CAPRICORN) and the Valsartan in Acute Myocardial Infarction Trial (VALIANT) were used to create a SCD risk model (with non‐SCD as a competing risk) in 13 202 patients. The risk model was validated in the Eplerenone Post‐AMI Heart Failure Efficacy and Survival Study (EPHESUS). The rate of SCD was 3.3 (95% confidence interval 3.0–3.5) per 100 person‐years over a median follow‐up of 2.0 years. Independent predictors of SCD included age > 70 years; heart rate ≥ 70 bpm; smoking; Killip class III/IV; left ventricular ejection fraction ≤30%; atrial fibrillation; history of prior myocardial infarction, heart failure or diabetes; estimated glomerular filtration rate < 60 mL/min/1.73 m 2 ; and no coronary reperfusion or revascularisation therapy for index AMI. The model was well calibrated and showed good discrimination (C‐statistic = 0.72), including in the early period after AMI. The observed 2‐year event rates increased steeply with each quintile of risk score (1.9%, 3.6%, 6.2%, 9.0%, 13.4%, respectively). Conclusion: An easy to use SCD risk score developed from routinely collected clinical variables in patients with heart failure, left ventricular systolic dysfunction or both, early after AMI was superior to left ventricular ejection fraction. This score might be useful in identifying patients for future trials testing treatments to prevent SCD early after AMI.